Hemoglobins S and C Interfere with actin remodeling in Plasmodium falciparum-infected erythrocytes - Cyrklaff, Marek; Sanchez, Cecilia P.; Kilian, Nicole; Frischknecht, Friedrich; Lanzer, Michael (Science, 2011)
The hemoglobins S and C protect carriers from severe Plasmodium falciparum malaria. Here, we found that these hemoglobinopathies affected the trafficking system that directs parasite-encoded proteins to the surface of infected erythrocytes. Cryoelectron tomography revealed that the parasite generated a host-derived actin cytoskeleton within the cytoplasm of wild-type red blood cells that connected the Maurer’s clefts with the host cell membrane and to which transport vesicles were attached. The actin cytoskeleton and the Maurer’s clefts were aberrant in erythrocytes containing hemoglobin S or C. Hemoglobin oxidation products, enriched in hemoglobin S and C erythrocytes, inhibited actin polymerization in vitro and may account for the protective role in malaria. The malaria parasite mines actin from the membrane skeleton of its erythrocyte host to generate a cytoskeletal structure.